Busıness Processes In The Insurance System And Theır Features - Kuzieva Nargiza Ramazanovna, Ashurova Nasiba Batirovna, Ollokulova Feruza Mansurovna (International Journal of Advanced Science and Technology, 2020)
The article discusses the need to implement business processes in the insurance system and its implementation in insurance companies. The theoretical and practical aspects of business processes in insurance companies are considered, and the methodology of business processes is described